#MoreThanAVisitor: Families as "Essential" Care Partners During COVID-19. (9th December 2020) - Kemp, Candace L
Abstract: The public health response to the current Coronavirus pandemic in long-term care communities, including assisted living, encompasses prohibiting visitors. This ban, which includes family members, has been criticized for being unfair, unhealthy, and unsafe. Against this backdrop, I examine the roles family play in residents' daily lives and care routines. I argue that classifying family as "visitors" rather than essential care partners overlooks their critical contributions and stems from taken-for-granted assumption about gender, families, and care work, and I demonstrate why families are more than visitors. Policies that ban family visits also reflect a narrow understanding of health that focuses on mitigating infection risk, but neglects overall health and well-being. This policy further stems from a limited comprehension of care relations. Research shows that banning family visits has negative consequences for residents, but also families themselves, and direct care workers. I argue that identifying ways to better understand and support family involvement is essential and demonstrate the utility of the Convoys of Care model for guiding the reconceptualization of family in long-term care research, policy, and practice during and beyond the pandemic.